Odpowiedzi

2010-03-05T17:04:17+01:00
-4k² - 16x + 9 = 0
-4k(2)-16x=-9

-4k(2)=-9+16x
k(2)=(-9+16x)/-4
k=pierwiastek z (-9+16x)/-4

-16x=-9+4k(2)
x=(-9+4k(2))/-16
2010-03-05T17:04:43+01:00
Tam chyba powinno byc x a nie k

-4x² - 16x + 9 = 0 /: (-1)
4x²+16x-9=0
delta=16²-4*4*(-9)=256+144=400
pierwiatek z delty=20

x=-16-20/8=-36/8=9/2=4 1/2=4,5 lub x=-16+20/8=4/8=0,5
2010-03-05T17:15:53+01:00
-4k² - 16x + 9 = 0

chyba chodzi o kwadratowe równanie(??/)

Δ=256+144=400
√Δ=20

x₁=36/(-8)=-4,5
x₂=-4/(-8)=0,5